2020
DOI: 10.1016/j.acra.2019.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Express Team-Based Learning (eTBL): A Time-Efficient TBL Approach in Neuroradiology

Abstract: IF-AT immediate feedback assessment technique iRAT individual readiness assurance test MCQ multiple choice question MEQ modified essay question PBL problem-based learning RAT readiness assurance tests TBL team-based learning tRAT team readiness assurance test 4 S's principle Significant, Same, Specific, Simultaneous Rationale and Objectives: Team-based learning (TBL) is a student-centred, teacher-directed instructional method that promotes active learning. The application phase of TBL stimulates group discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
2
21
0
1
Order By: Relevance
“…Moreover, the use of team-based learning andproblem-based learning improves their engagement and knowledge acquisition. This agrees with Smeby et al (2020) who reported that these strategies were rated significantly higher than traditional lectures on making difficult material comprehensible, increasing student engagement, and giving the students feedback on their own knowledge.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the use of team-based learning andproblem-based learning improves their engagement and knowledge acquisition. This agrees with Smeby et al (2020) who reported that these strategies were rated significantly higher than traditional lectures on making difficult material comprehensible, increasing student engagement, and giving the students feedback on their own knowledge.…”
Section: Discussionsupporting
confidence: 88%
“…In the homerooms, case-based learning was emphasized, and students had an opportunity to work through cases independently, ask questions, and clarify concepts. Active learning in the homeroom facilitated higher order cognitive skills as students could connect new knowledge and skills to existing knowledge (15)(16). Faculty were able to monitor student progress through the course and identify as well as address any potential knowledge gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Por fim, o professor conduz uma explanação do conteúdo discutido, revisando pontos essenciais e esclarecendo possíveis dúvidas dos estudantes (SMEBY et al, 2019;CARRASCO;BEHLING;LOPEZ, 2019).…”
Section: Abstract: Active Methodology Medical Education Team-based unclassified